Seasonal and Regional Characteristics of Aerosol Pollution in East and Southeast Asia - Nakata, Makiko; Mukai, Sonoyo; Yasumoto, Masayoshi (Frontiers in Environmental Science, 2018)
The atmospheric aerosol distribution in Asia is complex because it is influenced by both natural phenomena and human activities. In this article, multifaceted approach using satellite observations and numerical model simulation shows seasonal and regional variations of the aerosol distribution over Asia. Asia covers a large area; however, this article is limited to East and Southeast Asia. The aerosol optical thickness (AOT) in the inland desert area is normally high in spring and dusty aerosols are widely spread with the wind. The AOT values are high in summer over East Asia. A high AOT caused by biomass burning plumes is observed in autumn over Southeast Asia and in spring over Siberia and heavy air pollution occurs in Beijing in winter, a very well-known phenomenon. These phenomena caused by heavy aerosol concentration were determined based on Aqua/MODIS data and aerosol characteristics retrievals and estimated the aerosol characteristics. Furthermore, the impact of aerosols on the climate assessed by numerical model simulations suggest that aerosols reduce solar radiation and therefore the Earth’s surface temperature. In addition to these influences on the radiation budget, aerosols have a significant potential to change the circulation fields.